Taxi demand hotspots and customers’ travel destinations prediction using data mining approaches - Tan, Cheun Pin. (2012)
It has been estimated that over 23 thousand licensed taxis in Singapore are not occupied around 50 percent of driving time on average [4, 6]. Knowing taxi demand hotspots and customers’ travel destinations at a given time and location helps taxi drivers in daily planning and scheduling, as well as the taxi service provider in dispatching and also increases customers’ satisfactions toward taxi service.